Spironolactone for People Age 70 Years and Older With Osteoarthritic Knee Pain: A Proof‐of‐Concept Trial. Issue 5 (May 2016) - Mcmurdo, Marion E. T.; Sumukadas, Deepa; Donnan, Peter T.; Cvoro, Vera; Rauchhaus, Petra; Argo, Ishbel; Waldie, Helen; Littleford, Roberta; Struthers, Allan D.; Witham, Miles D.
Abstract : Objective: To determine whether spironolactone could benefit older people with osteoarthritis (OA), based on a previous study showing that spironolactone improved quality of life. Methods: This parallel‐group, randomized, placebo‐controlled, double‐blind trial randomized community‐dwelling people ages ≥70 years with symptomatic knee OA to 12 weeks of 25 mg daily oral spironolactone or matching placebo. The primary outcome was between‐group difference in change in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscale scores. Secondary outcomes included WOMAC stiffness and physical function subscores, EuroQol 5‐domain (EQ‐5D) 3L score, and mechanistic markers. Analysis was by intent to treat, using mixed‐model regression, adjusting for baseline values of test variables. Results: A total of 421 people had eligibility assessed, and 86 were randomized. Mean ± SD age was 77 ± 5 years and 53 of 86 (62%) were women. Adherence to study medication was 99%, and all participants completed the 12‐week assessment. No significant improvement was seen in the WOMAC pain score (adjusted treatment effect 0.5 points [95% confidence interval (95% CI) − 0.3, 1.3]; P  = 0.19). No improvement was seen in WOMAC stiffness score (0.2 points [95% CI −0.6, 1.1]; P  = 0.58), WOMAC physical function score (0.0 points [95% CI −0.7, 0.8]; P  = 0.98), or EQ‐5D 3L score (0.04 points [95% CI −0.04, 0.12]; P  = 0.34). Cortisol, matrix metalloproteinase 3, and urinary C‐telopeptide of type II collagen were not significantly different between groups. More minor adverse events were noted in the spironolactone group (47 versus 32), but no increase in death or hospitalization was evident. Conclusion: Spironolactone did not improve symptoms, physical function, or health‐related quality of life in older people with knee OA.